A simulation method for permeability of porous media based on multiple fractal model. (October 2015) - Tan, Xiao-Hua; Liu, Jian-Yi; Li, Xiao-Ping; Zhang, Lie-Hui; Cai, Jianchao
Abstract: Fluid flow in fractal porous media is a ubiquitous natural phenomenon which has received much attention over three decades in a wide variety of fields. In order to find a relationship between the pore of distribution and the permeability of porous media, a simulation method for the permeability of porous media is proposed based on the multiple fractal model. The pore size distributions and the permeabilities of the porous medium simulated by the presented method are compared with available experimental data. The validity of simulation method is obtained by the good agreement between the simulated results and the experimental data.